The General Election in Costa Rica, February 2010 - Wilson, Bruce M. (2011)
On 7 February 2010, almost 2 million Costa Ricans (69% of the registered electorate) voted in the country’s general election, the fifteenth consecutive general election to be held since the end of the short but bloody civil war of 1948. Laura Chinchilla was elected as Costa Rica’s first woman president but her Partido Liberación Nacional (National Liberation Party, PLN) fell short of a parliamentary majority and so will have to sustain agreements with other parties in the legislature in order to pursue its policy agenda.